Spontaneous poisoning by Trema micrantha (Ulmaceae) in goats - Traverso, Sandra Davi; Zlotowski, Priscila; Germer, Marlise; Cruz, Claudio Estevão Farias; Driemeier, David (Acta Scientiae Veterinariae, 2018)
Hepatotoxic plants are important cause of economical losses in farm animals in Brazil. This report concerns an outbreak of acute hepatic toxicosis, in which seven goats died after consumption of green leaves from a felled Trema micrantha tree. Two of these animals were necropsied and several tissues were processed for histological examination. Main histological finding was observed in the liver that showed centrilobular to massive necrosis consistent with an acute hepatic toxicosis. The overall picture was similar to those described in experimentally induced T. micrantha poisoning of goats. No additional known hepatotoxic plant was found in the paddock where the goats had been kept.